: Correlación de complicaciones metabólicas postquirúrgicas de manga gástrica vs bypass gástrico. Riobamba, 2018- 2020 - Aldaz Jaramillo, Jhonny German (2022)
Abstract Obesity as one of the most important challenges facing modern medicine has a high probability of becoming the main disease on which drastic measures should be taken, so that actions can be performed to improve the development and definitive prognosis of surgery. Objective: To determine the correlation of metabolic complications after gastric sleeve surgery vs gastric bypass, Social Security Ecuadorian Institute Hospital Riobamba, 2018 - 2020. Material and Methods: A descriptive cross-sectional study was performed to correlate the postoperative metabolic complications of bariatric surgery performed in patients in the surgery area of the Social Security Ecuadorian Institute Hospital Riobamba as an instrument of data collection, statistical records were applied with associated factors such as: sex, age, residence, occupation and pathological history in recent years. Results: An analysis was performed from 2018 to 2020 with a total of 47 patients, 21 women and 26 men. The distribution by age groups has objectified that the fourth decade of life is the group that includes the highest number of patients. Conclusions: Within bariatric surgery there is the possibility of several complications, depending on several aspects: type of surgical technique, postoperative evolution time, complications inherent to surgery and metabolic complications, emphasizing this issue by the supervision and control required later for a quick clinical recovery. Keywords: obesity, bariatric surgery, post-surgery, metabolic complications. Firmado electrónicamente por: WASHINGTON GEOVANNY ARMAS PESANTEZ Reviewed by: Mgs. Geovanny Armas Pesántez PROFESSOR OF ENGLISH C.C. 0602773301